OPTIMASI PARAMETER PROSES 3D PRINTING TERHADAP KEKUATAN TARIK FILAMEN PLA FOOD GRADE - Muhammad Habib Bari Bari; Pristiansyah Pristiansyah; Fajar Aswin (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Rapid prototyping technology, especially in three-dimensional printing, has been successfully used in many aspects. One of the rapid prototyping technologies that are often found in the market today is the type of FDM technology. FDM is a 3D printing technique for printing products using filament as a material. The filament used is food grade Polylactic Acid (PLA). This study aims to obtain optimal parameters to produce FDM printed objects in terms of tensile strength. The method used in the process of optimizing the parameters of this process is the Taguchi method L9 (33) OA. The process parameters used in this research are Temperature Nozzle, Layer Height, and Print Speed. The results showed that the optimal process parameter values ​​for tensile tests using food grade PLA filaments were Temperature Nozzle (210°C), Layer Height (0.1 mm) and Print Speed ​​(65 mm/s).